Evaluation of Conditions for the Development of Cryogenic Spinal Cord Injury Using a Canine Model: An Experimental Study on the Safety of Cryoablation for Metastatic Spinal Tumors - Kobayashi, Motoya; Kato, Satoshi; Demura, Satoru; Yokogawa, Noriaki; Yokka, Akira; Nakade, Yusuke; Annen, Ryohei; Gabata, Toshifumi; Tsuchiya, Hiroyuki (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Although the application of cryoablation to metastatic spinal tumors has been attempted, spinal cryoablation has the unique complication of cryogenic spinal cord injury. This study aimed to elucidate the conditions for the development of cryogenic spinal cord injury.MATERIALS AND METHODS: Fifteen canines were used in this study. A metal probe was inserted into the 13th thoracic vertebral body. Cryoablation was performed for 10 minutes by freezing the probe in liquid nitrogen. The control canine underwent probe insertion only. Spinal cord monitoring, epidural temperature measurement, motor function assessment, and pathologic examination of the spinal cord were performed.RESULTS: During the 10 minutes of cryoablation, the epidural temperature decreased and reached the lowest epidural temperature (LET) at the end of cryoablation. The LETs (degrees celsius [°C]) of each canine were −37, −30, −27, −8, −3, −2, 0, 1, 4, 8, 16, 18, 20, and 25, respectively. As the epidural temperature decreased, waveform amplitudes also decreased. At the end of cryoablation (10 minutes after the start of cryoablation), abnormal waves were observed in 92.9% (13/14) of canines. With epidural rewarming, the amplitude of the waveforms tended to recover. After epidural rewarming (2 hours after the start of cryoablation), abnormal waves were observed in 28.6% (4/14) of canines. The LETs (°C) of the canines with abnormal waves after epidural rewarming were −37, −30, −27, and −8. None of the canines with normal waves after epidural rewarming had any motor impairment. In contrast, all canines with remaining abnormal waves after epidural rewarming had motor impairment. In the pathologic assessment, cryogenic changes were found in canines with LETs (°C) of −37 −30, −27, −8, 0, and 1.CONCLUSIONS: This study showed that 10-minute spinal cryoablation with LETs (°C) of −37, −30, −27, −8, 0, and 1 caused cryogenic spinal cord injury. There was no evidence of cryogenic spinal cord injury in canines with LET of ≥4°C. The epidural temperature threshold for cryogenic spinal cord injury is between 1 and 4°C, suggesting that the epidural temperature should be maintained above at least 4°C to prevent cryogenic spinal cord injury.CMAPcompound muscle action potentialLETlowest epidural temperatureSCEPspinal cord–evoked potential